Adolescentes em cumprimento de medida socioeducativa de internação: um estudo sobre a escolarização no anos de 2016 e 2017 no centro de socioeducação de Foz do Iguaçu-PR - Ayala, Camila Soprani (2018)
This dissertation has as general object of study the public politics of schooling in the socioeducation in the State of Paraná. The theme involves effectiveness factors of the adolescents’ right to education who receive internment socio-educative measure. It was intended to reach out the following problem: would it be the Education for Youth and Adults – EJA modality adequate for the effectiveness of the schooling for adolescents who receive an internment socioeducational measure due to an infraction of the law? To replicate the problem, documentary and bibliographical research was developed qualitatively and quantitatively - once it reflected on social sciences and statistics - with analyzes of adolescents’ school data who fulfilled the internment measure in the Center of Socioeducation - CENSE from Foz do Iguaçu, considering primarily the age and the schooling stage reached before entering the internment measure. Thus, it was essential to have a vision that transits the nature of the interdisciplinary approach, since factors of schooling and socioeducation in the historical, legal and pedagogical scope were considered. Initially, the broad concept and legal basis of education and schooling modalities are presented, with descriptions of international and national historical landmarks. Thus, it goes into the context of schooling in the socioeducation, defining an infraction, modalities of socio-educational measures and the modality of schooling applied in the socioeducation, which is EJA. It is always pursuing public policies for the effectiveness of the schooling of the adolescent who is in the custody of the State due to internment socio-educational measure. Among the results presented, school dropout was confirmed in the age/grade relationship of these adolescents.